Analyzing Firm Performance: The Influence of Enterprise Risk Management, Investment Decisions, and ESG Aspects in ASEAN-5 Non Financial Firms - Muhammad Fikry Alfisyahrin; Dewi Hanggraeni (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine the effect of Enterprise Risk Management (Advanced level of ERM) and Investment Decisions on firm performance, with the moderating role of environmental, social and governance (ESG) factors in ASEAN-5 non-financial firms. Panel data regression analysis employed in this study with a total of 770 observations over a five-year period (2018 to 2022). The study finds a positive relationship between ERM implementation and firm performance metrics (ROA, Tobin's Q, PBV). Investment decisions, proxied by Price Earnings Ratio (PER), also show a positive influence on firm performance. Furthermore, Environmental, Social, and Governance (ESG) moderate the relationship between ERM on firm’s financial performance (ROA) and investment decisions on firm’s market performance (Tobin’s Q and PBV). The findings highlight the significance of integrating ESG factors on risk management practices and strategic investment decisions that improve firm’s financial and market-based performance.